The expression of NR2B subunit of NMDA receptor in the suprachiasmatic nucleus of Wistar rats and its role in glutamate-induced CREB and ERK1/2 phosphorylation - Bendová, Zdeňka; Sládek, Martin; Svobodová, Irena (Neurochemistry international, 2012)
Most behavioral and physiological processes in living organisms exhibit periodic circadian rhythmicity. In mammals, these rhythms are coordinated by the circadian clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus. In order to precisely synchronize free-running circadian oscillations to the 24h solar cycle, signals from the external environment, primarily the light/dark cycle, must reach the circadian clock within the SCN. A light pulse elevates intracellular Ca(2+) levels, and activates signaling cascades, leading to transcriptional activation of the clock genes mPer1 and mPer2 via phosphorylation of extracellular-signal-regulated kinases 1/2 (ERK1/2) and cyclic AMP-responsive element binding protein (CREB). Glutamate is the primary excitatory transmitter in retinal terminals in the SCN, and NMDA receptors (NMDAR) are the principal glutamate receptors that mediate the effect of light on resetting the circadian clock. Here we show the circadian rhythm in mRNA expression and protein level of the NMDAR 2B subunit (NR2B) in the SCN, with a peak at night. Also, we demonstrate ifenprodil inhibition of glutamate-induced phosphorylation of CREB (pCREB) and ERK1/2 (pERK1/2), and support thus the evidence for NR2B role in activation of signaling cascade involved in photic resetting of the circadian clock.
Keywords: Phosphorylation; In Situ Hybridization; fosforylace; hybridizace in situ; Suprachiasmatic Nucleus; Glutamic Acid; Receptors, N-Methyl-D-Aspartate; krysa rodu Rattus; zvířata; Excitatory Amino Acid Antagonists; potkani Wistar; Piperidines; receptory N-methyl-D-aspartátu; nucleus suprachiasmaticus; Rats, Wistar; Male; Cyclic AMP Response Element-Binding Protein; antagonisté excitačních aminokyselin; MAP Kinase Signaling System; protein vázající cAMP responzivní element; Rats; piperidiny; Animals; mužské pohlaví; MAP kinasový signální systém; kyselina glutamová